Research status quo of Traditional Chinese Medicine hot ironing therapy in the treatment of spleen and stomach diseases (中医热熨疗法治疗脾胃疾病的研究现状分析) - TIAN Xiaodong (田小冬); HUANG Yanping (黄砚萍); WANG Wenqing (王文清); WANG Ting (王婷) (中西医结合护理)
By searching ancient books and literature, this paper summarized the development history of Traditional Chinese Medicine hot ironing therapy and its treatment methods, therapeutic effects and application progress in spleen and stomach diseases, and to understand the research status of Traditional Chinese Medicine hot ironing therapy in the treatment of spleen and stomach diseases. Current researches findings showed that Traditional Chinese Medicine hot ironing therapy were effective in the treatment of spleen and stomach diseases, and more in-depth researches should be conducted to improve the clinical practice and ensure the therapeutic effect. (本文通过查找、检索有关热熨疗法的相关古籍及文献资料, 总结中医热熨疗法的发展历史, 以及脾胃疾病治疗方法、治疗效果和应用进展, 旨在了解中医热熨疗法在脾胃疾病中的研究现状。中医热熨疗法治疗脾胃疾病效果良好, 应不断深入研究, 使其能更好地发挥治疗效果。)